Trigger warning : a novel - Townsend, Jacinda (Graywolf Press, 2025)
"Early in life, Ruth survived a series of devastating events: Her little brother died from a childhood illness, her mother died of grief, and then her father was shot by the police right in front of their home. In the years following her father's murder, Ruth pushes her past underground. She changes her name and moves to Kentucky, marries a man named Myron, and together they raise a kid. It's been two decades, and she is, by outside measures, living a good life-but why doesn't it feel good? When her marriage comes to a sudden end, their house burns down in the middle of the night, and she learns that her estranged sister has been diagnosed with multiple sclerosis, Ruth is jolted back into action. She flees again, this time back to her home state of California, with her nonbinary teenager in tow, perhaps ready at last to face her pain and retrieve her former self. Searing, surprisingly witty, and deeply human, Trigger Warning is a novel about the durational aftermath of anti-Black police violence. Through the perspectives of Ruth and Myron, and those of their friends and their child, Townsend explores divorce and desire, the heartbreaking brevity of parenting, the push and pull of old friendships, and the possibility, after incredible trauma, of reconnecting to what makes us feel alive"--